Hadith Research Methodology in the Perspective of Syuhudi Ismail's Thought - Ach. Syafiq Fahmi; Intan Dwi Permatasari; Mas'ud; Faridatul Jannah (al-Bunyan: Interdisciplinary Journal of Qur'an and Hadith Studies, 2024)
This research aims to explore and analyze hadith research methodology from the perspective of Syuhudi Ismail, a Muslim scholar known for his contributions to hadith studies. In facing the complexity of contemporary challenges, hadith methodology has an important role in supporting the understanding and dissemination of Islamic teachings. Syuhudi Ismail, with his critical thinking approach, has made a significant contribution to the development of hadith research methodology. This research will identify the methodological principles proposed by Syuhudi Ismail, and explain the context of his thinking, using library research methods. The results of this research state that in Syuhudi Ismail's concept of thought, the object of hadith research is divided into 2, namely sanad research (Naqd al Khariji) and matan research (Naqd al-Dakhiliy). In sanad research (Naqd al Khariji), it begins with carrying out I'tibar al-Sanad and then continues with researching the personalities of the narrators and their methods of narration. In this research on sanad, Syuhudi mentions the elements of the rules for the validity of sanad in the simplified terms "major and minor rules". Meanwhile, in Matan Hadith research activities, Syuhudi gave several steps that researchers must take, including: 1). Examining the matan after looking at the quality of the sanad, 2) looking at the meaningful arrangement of the matan pronunciations, 3) examining the content of the matan, and concluding the results of the research on the matan hadith. The results of this research on hadith matan will revolve around two options, whether the matan hadith is shahih or dha'if.